Предмет: Алгебра,
автор: tannyy2013
решите уравнение (x-4) * ( x +4)-6x=(x-2)^2
Ответы
Автор ответа:
0
(x-4)(x+4)-6x=(x-2)^2
x^2-16-6x=x^2-4x+4
x^2-16-6x-x^2+4x-4=0
2x-20=0
x=10
x^2-16-6x=x^2-4x+4
x^2-16-6x-x^2+4x-4=0
2x-20=0
x=10
Автор ответа:
0
Пропустила - :x^2-16-6x-x^2+4x-4=0
-2x-20=0
x=-10
-2x-20=0
x=-10
Автор ответа:
0
cпасибо
Похожие вопросы
Предмет: Английский язык,
автор: ser200406228
Предмет: Геометрия,
автор: bkjr
Предмет: Литература,
автор: deksbeks3
Предмет: Алгебра,
автор: Пышуля
Предмет: Физика,
автор: Миша199920